Immunomodulation of nutritional formula containing epigallocatechin-3-gallate, ginseng extract, and polydextrose on inflammation and macrophage polarization - Wang, Yi; Hu, Yaozhong; Niu, Zhenhua; Zhang, Xuejiao; Fan, Dancai; Ji, Xuemeng; Lv, Huan; Wang, Shuo; Zhao, Yanrong (Frontiers in Nutrition, 2024)
Single nutrient like polyphenol or dietary fiber has been exhaustively investigated to validate the positive intervention on health or disease. Whereas, the common interaction of inner systems with nutrient complex has not been well elucidated, which raise the scientific issue of the modulatory effect of nutrient complex on immunity. The representative prebiotics of epigallocatechin-3-gallate (EGCG), ginseng extract and polydextrose (PDX) were selected on behalf of the classification of polyphenol, flavone or polysaccharides, and dietary fiber to generally cover the daily food intake in this study to explore their intervention on inflammation and macrophage polarization. Synergistic effect of selected nutrients was demonstrated by inhibiting M1 macrophage polarization, as well as the promotion on M2 macrophage polarization. Then, the nutrient formula was set up to verify the intervention effect, and the results revealed the significant inhibition on cell inflammation, as well as the effect on cell proliferation through promoting cell cycle in G2 phase. The nutrient complex could inhibit M1 macrophage polarization to inhibit M1 mediated inflammation, and promote M2 macrophages for antiinflammatory effect, and enhance cell phagocytosis. Whereas, the varied intervention effects of nutrient complex with different formula could be summarized. In general, the formula containing EGCG, ginseng extract and PDX was demonstrated to possess enhanced immunomodulatory effect on cell inflammation and macrophage polarization, which could potentially inspire the investigation of complexed nutrients on health and diseases.